Coronavirus SARS-CoV-2: infección, desarrollo, tratamiento y respuesta T (2020)
In December 2019, several cases of pneumonia patients were reported at a seafood market in Wuhan City, China. Although the origin of the virus is still unclear, SARS-CoV-2 is known to have 92% identity with the coronavirus found in lung samples from pangolin Manis javanica and 99% identity with the bat species Rhinolophus sinicus . This percentage of identity suggests that the virus originated in a bat and was transmitted to a human in an event known as zoonosis . Despite measures in different countries, the virus has managed to generate a pandemic, putting the health systems of several governments in crisis. As of the date of this writing, 17 September 2020, 17,106,007 confirmed cases with 668,910 deaths have been reported worldwide4, while in Colombia 295,508 confirmed cases and 10,105 deaths have been recorded.